1999
DOI: 10.1111/j.1601-0825.1999.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and oral disease: a critical review

Abstract: Hepatitis C virus (HCV) infection is widespread with an estimated 3% of the world population being infected.Acute infection is usually mild but chronicity develops in as many as 70% of patients, of whom at least 20% will eventually develop cirrhosis. A further 1-4% of cirrhotic individuals will develop hepatocellular carcinoma. Infection with HCV may have effects on various organs other than the liver. HCV has been causally associated with a remarkable array of extrahepatic manifestations, some of which remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 110 publications
(111 reference statements)
0
21
0
1
Order By: Relevance
“…Several reports have initially suggested an association between HCV and SS following the development of serological tests,[1415] which has been supported with more than 250 reported cases of SS–HCV. [35] Garcia-Carrasco et al .…”
Section: Sjogren's Syndrome and Salivary Gland Conditionsmentioning
confidence: 91%
See 2 more Smart Citations
“…Several reports have initially suggested an association between HCV and SS following the development of serological tests,[1415] which has been supported with more than 250 reported cases of SS–HCV. [35] Garcia-Carrasco et al .…”
Section: Sjogren's Syndrome and Salivary Gland Conditionsmentioning
confidence: 91%
“…Therefore, the probable association between HCV infection and OLP could not be proved initially. [15]…”
Section: Lichen Planusmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six variants of OLP which include papular, reticular, plaque-like, atrophic, erosive, and bullous disease. Erosive mucosal disease is most problematic given the pain associated with the disease and can lead to oral candidiasis as well as carry premalignant risk [51,52]. Occasionally, the only identifying clue in OLP can be the sole presence of Wickham's striae.…”
Section: Lichen Planusmentioning
confidence: 98%
“…In different studies, diseases such as ulcerative colitis, alopecia, areata, vitiligo, dermatomyositis, morphia, thymoma, myasthenia gravis, hypogammaglobulinemia and primary biliary cirrhosis are reported to occurredin lichen planus patients (Burns T 2004;Greenberg MS 2008). Some studies showed association of lichen planus with HIV and HCV (Gandolfo et al 1994;Roy and Bagg 1999;Klanrit et al 2003;Pilli et al 2002;Emadi et al 2010). Recent studies revealed that specific T lymphocytes related to chronic HCV infectionhave been defined in oral mucosa of chronic HCV and OLP patients (Pilli et al 2002).…”
Section: Association With Other Diseasesmentioning
confidence: 99%